2016
DOI: 10.1177/1475921715624502
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal analysis of crack patterns in reinforced concrete shear walls

Abstract: Conventionally, the assessment of reinforced concrete shear walls relies on manual visual assessment which is time-consuming and depends heavily on the skills of the inspectors. The development of automated assessment employing flying and crawling robots equipped with high-resolution cameras and wireless communications to acquire digital images and advance image processing to extract crack patterns has paved the path toward implementing an automated system which determines structural damage based on visual sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 28 publications
3
52
0
Order By: Relevance
“…The average carbonized depth and residual material intensity are conventional damage characteristic factors for reinforced concrete structures; Cao et al noticed that fractal damage factors have a linear correlation with the aforementioned conventional factors, and also monofractal and multifractal dimensions are indicators of damage in concentrated‐load space and even‐load space, respectively. Several studies showed that fractal dimension and multifractal dimensions are suitable parameters for damage classification and relative stiffness loss estimation of RCSWs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average carbonized depth and residual material intensity are conventional damage characteristic factors for reinforced concrete structures; Cao et al noticed that fractal damage factors have a linear correlation with the aforementioned conventional factors, and also monofractal and multifractal dimensions are indicators of damage in concentrated‐load space and even‐load space, respectively. Several studies showed that fractal dimension and multifractal dimensions are suitable parameters for damage classification and relative stiffness loss estimation of RCSWs …”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that fractal dimension and multifractal dimensions are suitable parameters for damage classification and relative stiffness loss estimation of RCSWs. 15,16 Although many researchers have indicated that fractal dimension is a strong indicator of damage, no one has yet proposed a robust predictive equation for damage assessment based on fractal dimension of the crack patterns. In this paper, using an extensive crack pattern database, a quantitative approach is developed to estimate the stiffness and strength loss by developing several predictive equations for various possible scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, SDNET2018 [21], with more than 56,000 labeled images of concrete structures, covers three small lab-made bridge decks, walls of a building, and several paved sidewalks, which are significantly smaller than common inspected infrastructures in practice. Manual identification of flaws in such large image sets is time consuming and prone to inaccuracy because of inspector fatigue or human error [22][23][24][25][26]. Image processing algorithms can improve the accuracy and efficiency of autonomous inspections by either (a) enhancing images to improve ease of human detection of defects or (b) autonomously identifying defects.…”
Section: Introductionmentioning
confidence: 99%
“…In geophysics, Posadas et al [24] characterize the dynamics of preferential water flow in soils and porous media with some particular parameters of multifractal spectra of MRI data. In engineering, multifractal spectra has been proposed as a method for evaluating the integrity of concrete shear walls through the study of images of fracture patterns caused by earthquakes [25]. They concluded that multifractal parameters move toward higher values as crack patterns extend and grow.…”
Section: Introductionmentioning
confidence: 99%